Impact of Neuroaxial Block on Hemodynamic Changes in Puerperas - Ye. M. Shifman; G. V. Filippovich; D. P. Antipin; V. Ye. Bukin; B. D. Vainshtein; V. Yu. Geronimus; A. V. Zhemchugov; I. Ye. Zarubina; A. L. Kalinin; A. B. Katsman; V. N. Maslak; V. N. Moshensky; et al. (Общая реаниматология)
The results of the multicentric study on «The safety of the spinal anesthesia during the caesarean section» describing the analysis of the hemodynamic changes due to neuroaxial block in parturients were presented. Thirteen clinics participated in the study. The volume of the sampling includes 2228 spinal anesthesia protocols. The study results confirm the consistency of some well-known regulations and standards of the safe performance of spinal anesthesia. Moreover, the following facts were revealed: the preinfusion during the spinal anesthesia does not have a preventive effect on arterial hypotension; the increase of the infusion volume results in elevating of the arterial hypotension frequency during spinal anesthesia; the bandaging of the lower extremities is a serious measure to prevent the hemodynamic complications; the application of 6% pentastarch solution for the postin-fusion is an effective method to prevent the arterial hypotension during spinal anesthesia for the cesarean section.